Pemenuhan Persyaratan Label Produk Pangan yang Dijual Secara Online terhadap Peraturan Label Pangan - Endah Ernawanti; Feri Kusnandar; Nur Wulandari (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Nowdays pre-packaged foods are not only marketed conventionally but also through online shops (e-commerce). Online sale food products must comply with Indonesian food labelling regulation to ensure their safety and quality. This study was aimed to evaluate the fulfilment of online food product labels, and the awareness of consumers that frequently purchase online food products. The most online food products that sold are dried food products which mostly produced by small medium enterprises (SMEs). Through the evaluation of labels from the food products sold in Tokopedia, there were only 412 (23%) products registered officially. Labels were further evaluated in terms of their conformity to the Labelling Regulation of Head of Indonesian National Agency of Drug and Food Control (NADFC) Number 12 Year 2016 and HK.03.1.23.04.12.2205 Year 2012. There were only 28% of food products (from those 23% of food products officially registered) that complied with the labelling regulation. Moreover, the analysis of consumer awareness for those who shopped in Tokopedia by surveying 56 respondent indicated that they were more concerned on the halal information of the food products.